Assessment of fetal nutrition status at birth using the clinical assessment of nutritional status score - Lakkappa, Lakshmi; Somasundara, Suguna (Indian Journal of Child Health, 2018)
Introduction: Assessment of fetal malnutrition (FM) among neonates has been a major concern to health personnel due to the potentially serious sequelae of malnutrition on multiple organ systems. There is a dearth of research in the use of a clinical assessment of nutritional (CAN) status score as a method of assessing FM in term newborns regarding the Indian context. Objective: This study was conducted to assess the FM by CAN score and to verify the validity of CAN score in relation to other anthropometric variables. Materials and Methods: A hospital-based observational study was carried out at a tertiary care hospital, Chamarajanagar, for a period of 3 months from March 2018 to May 2018. All liveborn, singleton term infants >37 weeks of gestation were included in the study. All measurements were carried out between 24 and 48 h of newborn age and data were collected using a structured questionnaire. Results: In this study, out of 250 neonates included, 52.8% of newborns were female and 47.2% were males. Total 8% of the study population was low birth weight, and 92% had normal birth weight. The CAN score of <25 was found in 21.2% while the rest of 78.8% of cases had CAN score of >25. CAN score had a sensitivity of 90%, specificity of 84.78%, and diagnostic accuracy of 85.2%. Conclusion: CAN score, a simple clinical index for identifying FM, is a good indicator than other anthropometric methods of determining intrauterine growth restriction like ponderal index.